2011
DOI: 10.1093/rpd/ncr056
|View full text |Cite
|
Sign up to set email alerts
|

CFD modelling of thoron and thoron progeny in the indoor environment

Abstract: Thoron (220Rn) exhalation from building materials has become increasingly recognised as a potential source for radiation exposure in residences. However, contrary to radon (222Rn), limited information on thoron exposure is available. The purpose of this study is to estimate the concentration of thoron and its progeny products in a typical Dutch living room using computational fluid dynamics. The predicted thoron concentration is ∼9 Bq m(-3) using a source term of 14 Bq s(-1) for the thoron exhalation from buil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…In these computations a thoron source of 4.35 Bq s À1 is applied to the room surfaces. The exhalation rate is theoretically derived and typical for the Dutch housing stock (De With and De Jong, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these computations a thoron source of 4.35 Bq s À1 is applied to the room surfaces. The exhalation rate is theoretically derived and typical for the Dutch housing stock (De With and De Jong, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years also advanced Computational Fluid Dynamics (CFD) models have been developed to model the dispersion of thoron (Chauhan et al, 2015) and its progeny as well as the attachment and deposition of the progeny nuclides (De With and De Jong, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Fi nite vol ume discretisation tech nique was im plemented in code to gen er ate the grid points. The air flow was as sumed to be in com press ible [15]. Fine mesh was used near the doors and the open ings, which gave the pre cise re sults with less com pu ta tional time.…”
Section: Cfd Mod El Ingmentioning
confidence: 99%
“…Thoron dis tri bu tion pat tern in in door en vi ronment is non-ho mog e nous un der the closed room condi tion with poor ven ti la tion [15,16]. Af ter re leas ing from room sur faces thoron gets dis trib uted in in door en vi ron ment along with spon ta ne ous de cay.…”
Section: Thoron Con Cen Tra Tion and Dif Fu Sion Length Pro Filementioning
confidence: 99%
“…It was shown that difference in source term of room surfaces led to in-homogeneity of radon distribution but on an average, simulation results were found to be close to experimental measurements. CFD model based results of indoor thoron distribution have not been validated experimentally (Urosevic et al, 2008;With et al, 2011). The objective of this study is to measure indoor thoron distribution and compare the results with CFD model predictions for a typical model room.…”
Section: Introductionmentioning
confidence: 99%